Temperature Affects Antagonism Among Coral-Associated Bacteria - Guo, Anjie; Li, Jie; Wang, Lin; Ju, Huimin; Li, Qiqi; Ren, Lijuan; Zhang, Si (Frontiers in Marine Science, 2022)
Reef-building corals are invertebrate animals that associate with diverse microorganisms, including Symbiodiniaceae, bacteria, fungi, and archaea. This symbiotic consortium, called the holobiont, is a dynamic system and rapidly responds to environmental temperatures. At present, the effects of temperature on bacteria-bacteria interactions in the coral-associated bacterial community are not clear. Antagonism is considered one of the potential structuring forces in coral microbial communities. Here, we examined the antagonistic interactions among 32 coral-associated bacteria and the physiological and biochemical characteristics of these isolates at different temperatures. The results showed that the antagonism breadth (i.e. the total number of antagonistic interactions) increased but antagonism intensity (i.e. the size of the inhibition zone) decreased at 32°C. The antagonistic interaction network was nested and sender-determined both at 25°C and 32°C, suggesting that the competition networks of coral-associated bacteria were more influenced by the antagonist strains than sensitive strains. Furthermore, we found that the elevated temperature increased the complexity of the antagonistic network. By evaluating the correlations between antagonism and the phylogenetic and phenotypic distances, we demonstrated that the antagonism probability correlated with the phylogenetic distance rather than phenotypic distance. Moreover, the antagonist strains have a wider metabolic niche space, i.e., grew on more carbon sources, than the antagonized strains at 25°C, while there was no difference at 32°C, suggesting the trade-off between antagonism and resource exploitation shifted in the antagonistic interactions under the higher temperature. These findings will be helpful for understanding the bacterial interactions in coral holobionts and the assembly of bacterial community in altered environments, especially under heat stress.